Psychopathology among youths who were victims of documented childhood maltreatment - Pinto, Ricardo (2014)
Background: There is an established relationship between childhood maltreatment and later psychopathology, but most studies have used self-reports and only consider a small number of experiences. The main aim of this study was to examine predictors of psychopathology by comparing two sources (official records vs. selfreports) of ten different childhood adversities among youths who were identified by Child Protective Services (CPS). We also used a comparison group that was not identified by CPS. This study also compared, in terms of psychopathology, three groups of respondents (under-report; agreement; and over-report) based on the discrepancy between the two sources of childhood adversity. Method: The sample included 136 youths, ages 14– 23 years, identified by CPS prior to age 12 as being maltreated and who lived with their family for at least 5 years. The comparison group included 80 youths. Results: The identified youths were not different from the comparison group in global psychopathology. Psychopathology was associated only with the total amount of self-reported adverse experiences, with depressive symptoms being predicted by both documented and selfreported sexual abuse. Females reported and had more documented adversities, presenting an increased risk for psychopathology. The under-report group had a higher mean of documented experiences and a lower mean in psychopathology. Conclusions: Despite the limitations of a self-report methodology, our findings attest to its contribution in predicting health outcomes. Professionals from CPS need to be thorough when assessing and documenting the multiple experiences that may co-occur in a household, paying particular attention when young girls are involved, as the experience of sexual abuse has been shown to be independently associated with later risk of developing depressive symptoms. This process may increase the appropriateness of the chosen interventions.